PENGARUH MOBIL ANGKUTAN UNTUK MENINGKATKAN EKONOMI KELUARGA DI KOTA SORONG PROVINSI PAPUA BARAT DAYA - Rosana Katelin Lekatompes,; Jajuk Suprijat,; Rinadini Hendrasworo, (Journal of Innovation Research and Knowledge, 2025)
This study examines how Public Transportation Fares, Transport Capacity, and Frequency of Transportation Services affect the Economic Improvement of families in Southwest Papua. High transportation costs in the region limit income opportunities, prompting the government to provide Special Transportation Mama-Mama Papua for affordable and accessible mobility. Using a quantitative approach with a descriptive and causal research design, data were collected from 63 of 75 users through questionnaires and analyzed via multiple linear regression in SPSS. The results indicate that fares, capacity, and service frequency significantly and positively influence the economic improvement of Southwest Papuan families, both partially and simultaneously